1990
DOI: 10.1037/0735-7036.104.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Multiple measures of motor lateralization in human primates (Homo sapiens).

Abstract: Laterality was assessed in 100 human (Homo sapiens) subjects through the use of five measures of motoric behavior in three categories: locomotor, manual, postural. Locomotor measures included leading limb for initiation of walking and whole-body turning. Performance and questionnaire measures were used to assess lateral hand bias. Postural bias was assessed as the weight distribution in quiet standing. Population-level biases on the manual and leading limb measures were to the right; on posture and turning, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
17
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 43 publications
4
17
0
1
Order By: Relevance
“…Walking, ascending, descending, and brachiating were the behavioral categories considered for locomotion, and sitting, lying, hanging, and changing postures were the ones associated with postural control. Whereas right-hand preferences in great apes and humans were previously reported for quadrupedal locomotion on a horizontal surface [Cunningham et al, 1989;Day & MacNeilage, 1996;Forsythe & Ward, 1987;Heestand, 1986;Hopkins & de Waal, 1995;Seltzer et al, 1990], one would expect preferences to emerge in more individuals in the case of climbing or walking on an incline (ascending and descending), as in other restrictive behaviors, since they involve starting from a more unstable position, which requires more balance and support control. Because going over an obstacle, descending to a lower level, and simply walking horizontally may require very different forms of muscular coordination, as they do in humans [Carpenter et al, 1998], the direction of the asymmetry in ascending and descending would not necessarily be the same as in walking.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Walking, ascending, descending, and brachiating were the behavioral categories considered for locomotion, and sitting, lying, hanging, and changing postures were the ones associated with postural control. Whereas right-hand preferences in great apes and humans were previously reported for quadrupedal locomotion on a horizontal surface [Cunningham et al, 1989;Day & MacNeilage, 1996;Forsythe & Ward, 1987;Heestand, 1986;Hopkins & de Waal, 1995;Seltzer et al, 1990], one would expect preferences to emerge in more individuals in the case of climbing or walking on an incline (ascending and descending), as in other restrictive behaviors, since they involve starting from a more unstable position, which requires more balance and support control. Because going over an obstacle, descending to a lower level, and simply walking horizontally may require very different forms of muscular coordination, as they do in humans [Carpenter et al, 1998], the direction of the asymmetry in ascending and descending would not necessarily be the same as in walking.…”
mentioning
confidence: 91%
“…The relevance of this is that hand preference in a specific task clearly could be intensified or even changed by a preexisting stable preference when one or another posture is adopted. In fact, lower-limb preferences in purely postural behaviors have been observed in several species of mammal, including bovines [Albright & Arave, 1997;Lane & Phillips, 2004;Phillips et al, 2003] and humans [Day & MacNeilage, 1996;Seltzer et al, 1990]. For example, in humans Seltzer et al [1990] found a group tendency in 100 individuals to distribute their body weight toward the left when standing, but only individual differences when turning around.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Στον ανθρώπινο πληθυσμό έχει μελετηθεί σε ενήλικες (Bestaven, Guillaud, & Cazalets, 2012;Bracha, Seitz, Otemaa, & Glick, 1987;Bradshaw & Bradshaw, 1988;Gordon, Busdiecker, & Bracha, 1992;Seltzer, Forsythe, & Ward, 1990; Tops, Wijers, Koch, & Korf, 2006), ενώ ελάχιστες είναι οι έρευνες που έχουν πραγματοποιηθεί σε παιδιά (Day & Day, 1997;Gospe, Mora, & Glick, 1990). Λόγω του ότι η περιστροφική κίνηση αντανακλά την ντοπαμίνεργικη δραστηριότητα στον εγκέφαλο, έχει επίσης εξεταστεί σε ανθρώπους με ψυχικές διαταραχές που πιθανόν να σχετίζονται με τη ντοπαμινική νευροχημεία (Bracha, 1987(Bracha, , 1991Bracha, Lyden, & Khansarinia, 1989;Bracha, Shults, Glick, & Kleinman, 1987;Lyon & Satz, 1991;Schneider, Calhoun, & Crosby, 1968).…”
Section: περιστροφική κίνησηunclassified